Sport and energy drinks consumption before, during and after training - Simulescu, V.; Ilia, G.; Macarie, L.; Merghes, P. (Science & Sports, 2019)
Aims: Sports drinks, when used by adult athletes, can have significant performance benefits. Sports drinks provide carbohydrates, electrolytes and fluids to the body, and help the body hydration, before, during, and after physical activity. The carbohydrates supply the muscles with fuel during exercise. The main electrolyte from sport drinks is sodium, which improves the drive to drink and can assist with fluid replacement. One of the main aim of using sport drinks is hydration, without decreasing sodium level in order to prevent hyponatremia. The addition of protein may be beneficial to prevent muscle damage and may improve or maintain subsequent performance over consecutive days. Other active ingredients (as vitamins) may play a role in energy metabolism or in free radical defense, but are usually found in small amounts and it is unclear if they have any direct performance benefits. Caffeine improves reaction time and if consumed few hours before anaerobic/resistance exercise may improve the performance, but has no effect on repeated high-intensity training. Conclusion: Sport drinks are useful only for adults athletes involved in endurance training, but are not recommended for children and adolescents. Sport drinks have the proper amounts and concentrations of carbohydrates and electrolytes to help the physical performance, in comparison with energy drinks, caffeinated energy drinks or other beverages.